THE ELEMENTS OF DRAMA IN IGBA NKWỤ: A TRADITIONAL WEDDING CEREMONY AMONG THE IGBO OF SOUTHEAST NIGERIA. - ONU, John Odo; OSEWA, Oludewa Roselyn (EBSU Journal of Social Sciences and Humanities, 2024)
This study explores the elements of drama in Ịgbankwụ wedding ceremony among the Igbo of southeast Nigeria. The objectives of the study are to showcase the dramatic and literary elements of Ịgbankwụ traditional wedding ceremony among the Igbo people of southeast Nigeria and how important they are in responding to social issues in the community. The study adopt a survey research design. The study is qualitative research with a descriptive paradigm. The study is premised on performance theory propounded by Schechner (2009). The data for the study was collected through observation, interviews and active participation. Data collected were analyzed descriptively. The findings of the study affirms the existence of drama in Ịgbankwụ, a traditional wedding ceremony among the Igbo people. Also, the following elements of drama were identified in igbankwu traditional wedding ceremony among Igbo people: plot, song and dance, costume, makeup, music, language, setting, performers, theme, character and characterization. It was also observed that education and religion are aspect of modernization that has affected the traditional wedding ceremony among the igbo people both positively and negatively.